Increased Cyclin Dependent Kinase in Aortic Tissue of Rats Fed Homocysteine - Lubec, Barbara; Arbeiter, Klaus; Hoeger, Harald; Lubec, Gert (Thrombosis and Haemostasis, 1996)
Background. Hyperhomocyst(e)inemia is strongly associated with occlusive arterial disease. Several mechanisms for the development of vascular lesions have been described. A direct effect of homocysteine on proliferation of smooth muscle cells and collagen expression was proposed recently. These observations led us to examine the effect of homocysteine on cyclin dependent kinase, the starter of mitosis and reflecting proliferation.Methods and results. Thirty Him: OF A rats were divided into three groups. Ten animals were fed for a period of six weeks 50 mg/kg body wt per day homocysteine, ten the same dose of homocysteic acid and ten remained untreated controls. At the end of the experiment we determined aortic cyclin dependent kinase, phosphokinases A and C, aortic homocyst(e)ine and aortic hydroxyproline. Aortic cyclin dependent kinase was significantly (p = 0.0001) elevated in the homocysteine treated group (mean 120 ± 15) compared with the homocysteic acid treated group (mean 71 ± 11) or the untreated group (mean 72 ± 10 fmol/mg aortic tissue). Aortic homocyst(e)ine was significantly higher in homocysteine treated animals (p = 0.0002) strongly correlating with cyclin dependent kinase (r squared = 0.85, p = 0.0001) and with aortic hydroxyproline (r squared = 0.66, p = 0.0001), which in turn was significantly (p = 0.0001) increased in the homocysteine treated group. Phosphokinases A and C determined to rule out nonspecific effects on kinases were not increased by administered homocysteine.Conclusions. Our findings indicate that homocysteine stimulates aortic cyclin dependent kinase with the possible consequence of proliferation of aortic cells. Aortic collagen accumulation could be explained by either the homocysteine-effect on collagen synthesis described in literature, or secondarily, by increased proliferation of collagen producing aortic cells.